Identification And Production Of Aren Plants Available At Gn. Riting Village, Membalong Subdistrict, Belitung - Tri Wahyuni; Sigit Puspito; Ahmadi Ahmadi; Ervina Ulva (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2022)
Sugar palm is a plant that has many benefits in human life. One of the most popular is water sap which is made to produce palm sugar, and even palm plants can also be produced to produce flour. This study aimed to identify the parts contained in the sugar palm plant and the sap produced by the sugar palm plant in GN Riting Village, Membalong Belitung District. This research was conducted to identify the parts contained in one sugar palm plant and the production of sap produced by sugar palm plants. The research method used in this study is a survey method with a sampling technique using purposive sampling. Based on the results of a survey conducted by researchers, the height of the sugar palm stem is 580 cm, the number of leaves is 11 leaves, the number of Mayang is seven female Mayang, 2-3 male Mayang, and fruit length is 39.8 cm, and the resulting sap production is 30 liters.